Use of substrates in the development of melon (Research, Society and Development, 2020)
The objective was to evaluate the performance of melon plant produced in different substrates. The melon hybrid variety used was “Ropey King” F1, submitted to the following treatments: T1 = Commercial substrate; T2 = goat manure and soil (3:1 v/v); T3 = sheep manure and soil (3:1 v/v); T4 = bovine manure and soil (3:1 v/v); T5 = organic compound and soil (3:1 v/v); T6 = earthworm humus and soil (3:1v/v). The design used was in randomized blocks with six treatments and four replications. The variables analyzed were: average emergence time, number of leaves, and height of the aerial part, root volume, root ball stability, fresh mass of the aerial, root and total parts, dry mass of the aerial, roots and total parts. According to the evaluations, the alternative substrates based on sheep manure and soil, and earthworm humus were the ones that promoted the best initial performance of the melon plant verified by the characteristics, height of the aerial part, volume of the root, fresh mass of the aerial, root and total parts, and dry mass of the aerial, roots and total parts.